AMPK phosphorylates ZDHHC13 to increase MC1R activity and suppress melanomagenesis - Sun, Y; Li, X; Yin, C; Zhang, J; Liang, E; Wu, X; Ni, Y; Arbesman, J; Goding, CR; Chen, S (American Association for Cancer Research, 2023)
Inherited genetic variations in the melanocortin-1 receptor (MC1R) responsible for human red hair color (RHC-variants) are associated with impaired DNA damage repair and increased melanoma risk. MC1R signaling is critically dependent on palmitoylation, primarily mediated by the protein acyltransferase ZDHHC13. A better understanding of how ZDHHC13 is physiologically activated could help identify approaches to prevent melanomagenesis in red-heads. Here we report that AMPK phosphorylates ZDHHC13 at S208 to strengthen the interaction between ZDHHC13 and MC1R-RHC, leading to enhanced MC1R palmitoylation in red-heads. Consequently, phosphorylation of ZDHHC13 by AMPK increased MC1R-RHC downstream signaling. AMPK activation and MC1R palmitoylation repressed UVB-induced transformation of human melanocytes in vitro and delayed melanomagenesis in vivo in C57BL/6J-MC1R-RHC mice. The importance of AMPK to MC1R signaling was validated in human melanomas where AMPK upregulation correlated with expression of factors downstream from MC1R signaling and with prolonged patient survival. These findings suggest AMPK activation as a promising strategy to reduce melanoma risk, especially for individuals with red hair.